Zwitterionic DNA: enzymatic synthesis of hypermodified DNA bearing four different cationic substituents at all four nucleobases - Kuprikova, Natalia; Ondruš, Marek; Bednárová, Lucie; Kraus, Tomáš; Slavětínská, Lenka Poštová; Sýkorová, Veronika; Hocek, Michal (Nucleic acids research, 2025)
We designed and synthesized a set of four 2'-deoxyribonucleoside 5'-O-triphosphates (dNTPs) bearing cationic substituents (protonated amino, methylamino, dimethylamino and trimethylammonium groups) attached to position 5 of pyrimidines or position 7 of 7-deazapurines through hex-1-ynyl or propargyl linker. These cationic dNTPs were studied as substrates in enzymatic synthesis of modified and hypermodified DNA using KOD XL DNA polymerase. In primer extension (PEX), we successfully obtained DNA containing one, two, three, or (all) four modified nucleotides, each bearing a different cationic modification. The cationic dNTPs were somewhat worse substrates compared to previously studied dNTPs bearing hydrophobic or anionic modifications, but the polymerase was still able to synthesize sequences up to 73 modified nucleotides. We also successfully combined one cationic modification with one anionic and two hydrophobic modifications in PEX. In polymerase chain reaction (PCR), we observed exponential amplification only in the case of one cationic modification, while the combination of more cationic nucleotides gave either very low amplification or no PCR product. The hypermodified oligonucleotides prepared by PEX were successfully re-PCRed and sequenced by Sanger sequencing. Biophysical studies of hybridization, denaturation, and circular dichroism spectroscopy showed that the presence of cationic modifications increases the stability of duplexes.
Keywords: Polymerase Chain Reaction; DNA-dependentní DNA-polymerasy; DNA; kationty; Cations; Deoxyribonucleotides; DNA-Directed DNA Polymerase; deoxyribonukleotidy; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions; polymerázová řetězová reakce